2020- تقييم دور الصكوك الإسلامية في تنمية سوق أدوات الدين الماليزي خلال الفترة 2008: Evaluation of the role of Islamic instruments in the development of the Malaysian debt instruments market during 2008-2020. - صابر رشيد; نورين بومدين (Journal of North African Economies, 2025)
This study aims to assess Malaysian experience in the issuance of Islamic sukuk through an analytical study of the market for Islamic instruments and traditional bonds, and a comparison of the evolution of their volumes over the period 2008-2020. The study concluded that the overall volume of universal issuance of sukuk had evolved significantly during the study period, In particular, in Malaysia, the volume of issuance of sukuk has seen some progress compared to bonds, particularly in recent years following the measures taken by the Malaysian authorities to encourage the market for instruments at the expense of bonds, However, a small proportion of the evolution in the volume of instruments returns to improved instrument performance, and the increasing ratio of sukuk to bonds is due to the decline in bond performance due to the recession in the world in recent years as oil prices decline, Malaysia's experience is avant-garde, but it still needs more care, The volume of issuance of sukuk is low compared to the size of property tools, other measures must therefore be taken to increase the volume of instruments issued in order to be more competitive relative to the volume of ownership tools.